Trichoepithelioma - Siddharth P Mosby; M N Naidu; S G Ranpise; Shaliputra Magar (Wolters Kluwer Medknow Publications, 2011)
Trichoepithelioma-a small benign tumor derived from basal cells in the hair follicle. It may occur sporadically or as the cardinal feature of a relatively common genetic disorder called multiple familial trichoepithelioma characterized by the presence of many small tumors predominantly on the face, inherited in an autosomal dominant pattern. A trichoepithelioma can undergo malignant transformation into a basal cell carcinoma. 1 This is a case report of 66-year-old male patient with a rounded and mobile firm swelling of 1 cm on mandibular labial vestibule of the oral cavity causing alarm and discomfort to the patient.